STUDY AL-QURAAN: Understanding Verses That Has Meaning Ta'arud - Malik, Jamaluddin (Perhimpunan Sarjana Ekonomi dan Bisnis, 2021)
Ta ' âruđ is a dispute between arguments in giving law. There are some scholars who interpret the word ta'âruđ with contradiction. So it is very reasonable if in the final conclusion they argue that there is no ta'âruđ in the Qur'an. On the other hand, there are also scholars who interpret it as a dispute. So that in the final conclusion it is very possible to have ta'âruđ in the Qur'an. The verse that is discussed using this method is the verse that talks about guidance, namely whether or not humans can give it. Then the verse that discusses whether or not it is permissible for Muslims to leave fasting because they are sick or on a long trip. The next discussion is about the verse that discusses the iddah of a woman whose husband died while she was pregnant. As an example of the discussion of the verse, it can be said that ta'âruđ in the Qur'an really exists with the meaning of disagreement, not conflict. Because after all, the Qur'an is the holy book of Muslims that comes from God so there can be no contradiction between the verses in it.